(untitled) (Sains Humanika, 2014)
Teachers who apply the contextual teaching approach can help students master agricultural science subject comprehensively and meaningfully, thus increasing students’ interest in venturing the field of agriculture. Knowledge and attitude of teachers were found to influence teacher’s implementation of teaching approach that being carried out in classroom. The purpose of this study is to determine teacher’s level of contextual knowledge and the relationship between knowledge and attitude of agricultural science teachers towards contextual teaching. Research respondents were 35 agricultural science teachers in national-type secondary schools. The research instrument was designed based on related past studies. Study result discovered agricultural science teachers had high level of knowledge and positive attitude towards contextual teaching. There was a significant relationship, r = .667 between knowledge and attitude of agricultural science teachers and contextual teaching, followed by a significant relationship between agricultural science teachers’ knowledge r = .368 and attitude, r = .523 with frequent contextual teaching approach practice. In conclusion, knowledge and attitude were two variables that determine the practice of contextual approach among teachers.